Comparison of Duplex and Quadruplex Folding Structure Adenosine Aptamers for Carbon Nanotube Field Effect Transistor Aptasensors - Nguyen, Hong Phan T.; Murugathas, Thanihaichelvan; Plank, Natalie O. V. (Nanomaterials (Basel, Switzerland), 2021)
Carbon nanotube field effect transistor (CNT FET) aptasensors have been investigated for the detection of adenosine using two different aptamer sequences, a 35-mer and a 27-mer. We found limits of detection for adenosine of 100 pM and 320 nM for the 35-mer and 27-mer aptamers, with dissociation constants of 1.2 nM and 160 nM, respectively. Upon analyte recognition the 35-mer adenosine aptamer adopts a compact G-quadruplex structure while the 27-mer adenosine aptamer changes to a folded duplex. Using the CNT FET aptasensor platform adenosine could be detected with high sensitivity over the range of 100 pM to 10 µM, highlighting the suitability of the CNT FET aptasensor platform for high performance adenosine detection. The aptamer restructuring format is critical for high sensitivity with the G-quadraplex aptasensor having a 130-fold smaller dissociation constant than the duplex forming aptasensor.